Gum induction from arid tree species an alternative source of income - K., Shiran; Verma, Archana; Pareek, Kamlesh; Kumar, Praveen (Indian Farming, 2018)
For collection of gum tears first allow them to dry on the tree itself for 5 to 7 days, once tears are semisolid they can be removed by hand from lower parts of the tree.